2016
DOI: 10.3389/fncel.2016.00106
|View full text |Cite
|
Sign up to set email alerts
|

Selective Localization of Shanks to VGLUT1-Positive Excitatory Synapses in the Mouse Hippocampus

Abstract: Members of the Shank family of multidomain proteins (Shank1, Shank2, and Shank3) are core components of the postsynaptic density (PSD) of excitatory synapses. At synaptic sites Shanks serve as scaffolding molecules that cluster neurotransmitter receptors as well as cell adhesion molecules attaching them to the actin cytoskeleton. In this study we investigated the synapse specific localization of Shank1-3 and focused on well-defined synaptic contacts within the hippocampal formation. We found that all three fam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
26
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 51 publications
6
26
0
Order By: Relevance
“…This did not reveal co-immunolabeling ( Supplementary Fig. 2b), consistent with earlier evidence for nonoverlapping distribution of vGlut1 and vGlut2 (Heise et al 2016), and demonstrating that these 2 populations of excitatory subicular neurons project onto the same superficial layers of RSC. Overall, projection from vGlut1 + and vGlut2 + neurons labeled by infusing virus with cannula into DH ( Supplementary Fig.…”
Section: Projections From Dh To Rsc Are Molecularly Distinctsupporting
confidence: 90%
“…This did not reveal co-immunolabeling ( Supplementary Fig. 2b), consistent with earlier evidence for nonoverlapping distribution of vGlut1 and vGlut2 (Heise et al 2016), and demonstrating that these 2 populations of excitatory subicular neurons project onto the same superficial layers of RSC. Overall, projection from vGlut1 + and vGlut2 + neurons labeled by infusing virus with cannula into DH ( Supplementary Fig.…”
Section: Projections From Dh To Rsc Are Molecularly Distinctsupporting
confidence: 90%
“…This study utilized confocal microscopy to examine developmental SHANK1 co‐expression with various cellular markers in the hippocampus, a critical brain region for learning and memory. Consistent with numerous studies, our findings demonstrated that SHANK1 strongly co‐expressed with the dendritic marker MAP2 (Lim et al, ; Naisbitt et al, ; Hung et al, ; Heise et al, ). Furthermore, our subsequent analyses demonstrated that SHANK1 MAP2 co‐expression peaked at P15, suggesting an increased amount of SHANK1 localized to CA1 dendrites.…”
Section: Discussionsupporting
confidence: 92%
“…Shank2, which is mainly localized at excitatory synapses (Boeckers et al, 1999 ; Tao-Cheng et al, 2015 ; Heise et al, 2016 ), may regulate excitatory synapse formation and function in dendrites and consequently the output functions of PV-positive neurons, suggesting a potential mechanism for the resistance to PTZ-induced seizures in Pv-Cre;Shank2 fl/fl mice. Notably, excitatory transmission, neuronal firing, and inhibitory transmission to target neurons are reduced in PV-positive neurons in Shank1 global KO mice (Mao et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%